(untitled) (Jahangirnagar University Journal of Biological Sciences, 2018)
An experiment was conducted with Labeo bata fry for 60 days to examine the growth performance and survival in response to three supplementary feeds i.e. wheat bran, maize bran and mixed diet. The length gain, percent length gain, weight gain, percent weight gain and specific growth of the fry were found significantly higher (p<0.05) in mixed diet. The highest survival rate (74.38±8.1%) was shown by the mixed diet treated fry which was significantly higher than those of maize bran and wheat bran treated fry respectively. There were no significant differences (p<0.05) among the treatments in term of water temperatures, pH and dissolved oxygen (DO). Thus, on the basis of the fry growth performance and survival rate, it could be suggested that the mixed diet of wheat bran and maize bran is suitable for the culture of L. bata fry. Jahangirnagar University J. Biol. Sci. 7(1): 15-21, 2018 (June)